The Effect of Buteyko Breathing Technique on Anxiety in Patients with Bronchial Asthma - Dede Andriyani Masmala Putri; Budi Antoro; Hernida Warni (Inspirasi Foundation, 2027)
Introduction: Anxiety is an unpleasant feeling condition, full of restlessness, tension and abnormal hemodynamic symptoms as a result of sympathetic, parasympathetic and endocrine stimulation. One effort to reduce anxiety levels in asthma patients is with breathing relaxation techniques. This relaxation technique is known to be effective in reducing anxiety for the treatment and prevention of respiratory disorders, hyperventilation and shortness of breath. Objective: Purpose of this study was to determine the effect of the Buteyko breathing technique on the anxiety of bronchial asthma patients at Graha Husada Hospital Bandar Lampung. Method: Type of research is Quantitative with a Pre-test and post-test design. The population in this study were 28 bronchial asthma patients in January 2025. So that a sample of 28 respondents was obtained. The sample technique in this study used nonprobability sampling with the Consecutive sampling technique. Result: results obtained before being given therapy were 20 respondents (71.0%) who had mild anxiety levels. It is known that from 28 respondents, the results obtained after being given therapy were 28 respondents (100.0%). It is known that the results of the statistical test with the Paired T-test obtained p = 0.001 (p <0.05) which means that there is an Effect of Buteyko Breathing Technique on Anxiety in Bronchial Asthma Patients at Graha Husada Hospital, Bandar Lampung. Conclusion: It is known that the results of the statistical test with the Paired T-test obtained p = 0.001 (p <0.05) which means that there is an influence of the Buteyko Breathing Technique on the anxiety of bronchial asthma patients at Graha Husada Hospital, Bandar Lampung.